Artificial Intelligent applications for mental health support: a review paper - Khalaf, Ayesheh Ahrari; Hassan Abdalla Hashim, Aisha; Olowolayemo, Akeem; Olanrewaju, Rashidah Funke; ,; , (Kulliyyah of Engineering, IIUM, 2021)
Mental health is every human's right. Physical health cannot be achieved without a healthy mind. Good mental health helps dealing with the stress of life, affects physical health, and allows building and maintaining strong human relationships. Individuals with a healthy mind can be a valuable part of society and contribute to their community while feeling fulfilled and satisfied. While its importance is obvious, almost everyone at some points in their lives faces some life-altering experiences that could challenge their mental health, such as trauma, abuse and family problems, genetics, and lifestyles. At the moment, the treatment options are majorly limited to attending psychotherapy, medical therapy, and self-help. Unfortunately at the moment, the option of attending a psychotherapy session is not available or affordable for everyone around the world. Also, accessibility to professional therapists is limited. Besides that even though therapists are trained to be unbiased and fair, it is always harder for humans to overcome their personal preferences and biases. Sometimes that is way easier to control and manipulate with machines. This paper will review the latest advancements in technology, from mobile applications to robots, that are designed to help with mental health matters.